Milk β‐casein as delivery systems for luteolin: Multi‐spectroscopic, computer simulations, and biological studies. Issue 7 (25th March 2022) - Cheng, Ye; Liu, Dan; Zeng, Meng; Chen, Junliang; Mei, Xueying; Cao, Xiangyu; Liu, Jianli
Abstract: β‐Casein, a highly amphiphilic calcium‐sensitive phosphoprotein, has specific features that promote its application as a nanocarrier for hydrophobic bioactives. Luteolin is a flavonoid with rich biological activities existing in vegetables and fruits. It is important to understand the interaction of β‐casein with luteolin for the development of β‐casein‐based delivery systems. Here, the interaction mode between luteolin and β‐casein was investigated with multispectral techniques, computer simulation, and biological methods. The results demonstrated that luteolin could bind to β‐casein spontaneously which is driven by hydrophobic interactions and statically quench the intrinsic fluorescence of β‐casein. Molecular docking and molecular dynamics simulation showed that β‐casein formed a stable complex with luteolin. It could be concluded that luteolin was encapsulated in β‐casein micelles and exhibited higher antioxidant activity than luteolin alone. These results would be helpful to understand the interaction mechanism of luteolin with β‐casein and indicated that β‐casein micelles were very promising as delivery vehicles for luteolin. Practical applications: Adding bioactive compounds to food is an efficient method of functional food processing, and protein is an excellent natural carrier for these substances. β‐Casein is a milk protein with a unique amphiphilic structure that makes it a natural nanocarrier for active ingredients. This study created β‐casein nanocarriers and encapsulated luteolin based on the interaction mechanism between β‐casein with luteolin. Luteolin encapsulated in β‐casein micelles demonstrated higher antioxidant activity when compared to free luteolin. This research will provide useful data for the development of functional foods based on β‐casein and luteolin in the food industry. Abstract : The spontaneous combination of β‐casein and luteolin leads to the potential of β‐casein as a carrier of luteolin and enhances its antioxidant activity.